2013
DOI: 10.1155/2013/405708
|View full text |Cite
|
Sign up to set email alerts
|

Diversity and Antimicrobial Properties of Lactic Acid Bacteria Isolated from Rhizosphere of Olive Trees and Desert Truffles of Tunisia

Abstract: A total of 119 lactic acid bacteria (LAB) were isolated, by culture-dependant method, from rhizosphere samples of olive trees and desert truffles and evaluated for different biotechnological properties. Using the variability of the intergenic spacer 16S-23S and 16S rRNA gene sequences, the isolates were identified as the genera Lactococcus, Pediococcus, Lactobacillus, Weissella, and Enterococcus. All the strains showed proteolytic activity with variable rates 42% were EPS producers, while only 10% showed the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
58
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 73 publications
(62 citation statements)
references
References 64 publications
(66 reference statements)
2
58
0
2
Order By: Relevance
“…Characteristic polypeptide bands appeared in the WC cheese, which showed the most complex profile. The contribution of W. cibaria to proteolysis in cheeses or other fermented foods (e.g., sourdough, table olives) was previously described (Capuani et al, 2013;Fhoula et al, 2013). As previously shown (Coda et al, 2006), primary proteolysis of Italian Pecorino cheeses was characterized by the intense or complete hydrolysis of α S1 -CN, which indicated considerable chymosin activity.…”
Section: Proteolysismentioning
confidence: 83%
“…Characteristic polypeptide bands appeared in the WC cheese, which showed the most complex profile. The contribution of W. cibaria to proteolysis in cheeses or other fermented foods (e.g., sourdough, table olives) was previously described (Capuani et al, 2013;Fhoula et al, 2013). As previously shown (Coda et al, 2006), primary proteolysis of Italian Pecorino cheeses was characterized by the intense or complete hydrolysis of α S1 -CN, which indicated considerable chymosin activity.…”
Section: Proteolysismentioning
confidence: 83%
“…In contrast, the antibacterial activity of IMAU80087 cell-free supernatant was not affected by such pH adjustment; and its activity against Escherichia coli O157:H7 was even enhanced after the pH change. Although it has previously been suggested that LAB antibacterial activities against Gram-negative bacteria are related to the organic acid effect or other bioactive materials, which have a potent effect at acidic range (Fhoula et al 2013), results from strains IMAU80076, IMAU70104, and IMAU80087 illustrated that other bacterial inhibitory mechanisms may be involved.…”
Section: Effect Of Different Treatments On Antibacterial Property Of mentioning
confidence: 97%
“…Per se, the genera Lactobacillus is not a plant growth promoting rhizobia (PGPR) but few results have shown their presence in rhizosphere [21] and has plant-growth promoting activity [22] presumably due to its active secretions. We believe that it may be due to its antibacterial activities, secretion of vitamins and other co-factors due to which they display beneficial properties in the mammalian gut.…”
Section: Biochemical and Microbial Analysis Of Organic Manuresmentioning
confidence: 99%